Pengaruh Rasio Likuiditas, Solvabilitas Dan Aktivitas Terhadap Pertumbuhan Laba Pada Perusahaan Sub Sektor Otomotif Yang Terdaftar Di Bei - Dasriyan Saputra (Pusat Riset dan Inovasi Nasional, 2023)
This study was conducted to analyze and determine the effect of the current ratio (X1), debt to equity ratio (X2) and total asset turnover (X3) partially and simultaneously on profit growth (Y) in the automotive sub-sector listed on the IDX for the period 2017 - 2022. Research data is sourced from the official website of the IDX and the company's official website. The population of this study were 12 automotive companies listed on the Indonesia Stock Exchange for the period 2017-2022. The sample was taken using a purposive sampling technique and 6 automotive companies were sampled. Data analysis used purposive sampling technique using IBM SPSS Statistics 26 software for windows. The results of the study show that the current ratio partially has no positive and insignificant effect on profit growth, the results of the debt to equity ratio partially have no positive and insignificant effect on profit growth and the results of total asset turnover partially have no positive and insignificant effect on profit growth. Simultaneously the current ratio, debt to equity ratio and total asset turnover have a significant influence on profit growth.